The Effect of Morning and Evening Aerobic Gymnastics Training towards Blood Hemoglobin Level Enhancement on Adolescence Girls - Anifatul Dicka Wahyu Setyaningrum; Sugiyanto Sugiyanto; Noer Rachma (Kazimierz Wielki University, 2019)
Background: The purpose of this research was to know and to analyze (1) the different effect of aerobic gymnastics training in the morning and in the evening toward blood hemoglobin level, (2) the different of enhancement of blood hemoglobin level between beginning and the end adolescence age group, (3) interaction effect between training times with adolescence age group towards blood hemoglobin level. Subject and Method: This research employed an experimental method consisting of independent variables and dependent variable. The research used experimental method with 2x2 factorial design. The population in this research was all female students from Muhammadiyah Vocational high school and junior high school Kradenan Blora, Central Java. Result: The results of ANAVA test obtained p-value calculated on amount of aerobic gymnastics training time-giving0,041 < sig. alpha 0,05 it means that there was a difference of blood hemoglobin level on night and morning aerobic gymnastics training. The results of the test in the age group of adolescence obtained the p-value amount 0.039 < sig. alpha 0.05, it means that there was a difference of blood hemoglobin level on the group of the early and late adolescence age. The result of interaction test (A X B) obtained p-value amount 0.028 < sig. alpha 0.05, it means that there was interaction effect between aerobic gymnastic training time-giving and adolescence girl age group. Conclution: The combination of aerobic gymnastic training time-giving and adolescence girl group age is taking effect towards blood hemoglobin level.